Berbamine inhibits Japanese encephalitis virus (JEV) infection by compromising TPRMLs-mediated endolysosomal trafficking of low-density lipoprotein receptor (LDLR) - Lihong Huang; Huanan Li; Zuodong Ye; Qiang Xu; Qiang Fu; Wei Sun; Wenbao Qi; Jianbo Yue (Emerging Microbes and Infections)
Japanese encephalitis virus (JEV), a member of the Flavivirus genus, is an important pathogen that causes human and animal infectious diseases in Asia. So far, no effective antiviral agents are available to treat JEV infection. Here, we found that LDLR is a host factor required for JEV entry. Berbamine significantly decreases the level of LDLR at the plasma membrane by inducing the secretion of LDLR via extracellular vesicles (EVs), thereby inhibiting JEV infection. Mechanistically, berbamine blocks TRPMLs (Ca2+ permeable non-selective cation channels in endosomes and lysosomes) to compromise the endolysosomal trafficking of LDLR. This leads to the increased secretion of LDLR via EVs and the concomitant decrease in its level at the plasma membrane, thereby rendering cells resistant to JEV infection. Berbamine also protects mice from the lethal challenge of JEV. In summary, these results indicate that berbamine is an effective anti-JEV agent by preventing JEV entry.